Kid-friendly TODs - Robert Cervero; Cathleen Sullivan (University of California, Institute of Urban and Regional Development (IURD), 2010)
Transit-oriented developments, or TODs, are commonly thought to appeal to non-traditional households. This paper reviews experiences with TODs, drawn mainly from Europe, that are kid-friendly. What makes them attractive to families are extensive shared green spaces and playgrounds in lieu of surface parking, no-traffic zones, and ample play spaces and cycling paths. Mixed land uses, high-levels of nearby transit services, and defensible spaces also have appeal. In some instances, higher rents reflect these benefits. Reducing on-site parking requirements and introducing transfer mechanisms that help cover the higher costs of family-size affordable units near rail stops can help promote kid-friendly TODs.
Keywords: 330